2006
DOI: 10.1371/journal.pbio.0040303
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Supergene Locus Controls Colour Pattern Diversity in Heliconius Butterflies

Abstract: We studied whether similar developmental genetic mechanisms are involved in both convergent and divergent evolution. Mimetic insects are known for their diversity of patterns as well as their remarkable evolutionary convergence, and they have played an important role in controversies over the respective roles of selection and constraints in adaptive evolution. Here we contrast three butterfly species, all classic examples of Müllerian mimicry. We used a genetic linkage map to show that a locus, Yb, which contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
391
4
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(406 citation statements)
references
References 39 publications
10
391
4
1
Order By: Relevance
“…Therefore, recombination between both genes occurred in none of the individuals. Moreover, we found that the candidate regions of both genes shared correspondence with a region associated with wing-and body-colour variations in different lepidopteran species, that is, B. betularia, Heliconius cydno, Heliconius erato, Heliconius melpomene and Heliconius numata (Joron et al, 2006;Kronfost et al, 2006;Papa et al, 2008;Ferguson et al, 2010;van't Hof et al, 2011). These results strongly suggest that the same genes and/or regulatory elements responsible for wing and body colour in Bombyx, Bm and Ws, may underlie these variants in different Lepidoptera.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Therefore, recombination between both genes occurred in none of the individuals. Moreover, we found that the candidate regions of both genes shared correspondence with a region associated with wing-and body-colour variations in different lepidopteran species, that is, B. betularia, Heliconius cydno, Heliconius erato, Heliconius melpomene and Heliconius numata (Joron et al, 2006;Kronfost et al, 2006;Papa et al, 2008;Ferguson et al, 2010;van't Hof et al, 2011). These results strongly suggest that the same genes and/or regulatory elements responsible for wing and body colour in Bombyx, Bm and Ws, may underlie these variants in different Lepidoptera.…”
Section: Introductionmentioning
confidence: 81%
“…The genetic and genomic analysis demonstrated the following: (i) the candidate regions of the Bm and Ws genes are located in~2-Mb-long and 100-kb-long regions on the same scaffold Bm_scaf33 of chromosome 17; (ii) chromosome 17 of Bm mutation harbours inversion within a compartment corresponding to Bm_scaf33; and (iii) the Bm and Ws regions share synteny with a region associated with wing-and body-colour variations in different lepidopteran species (Joron et al, 2006;Kronfost et al, 2006;Papa et al, 2008;Ferguson et al, 2010;van't Hof et al, 2011). Based on our results, we hypothesise that this common region may control wingand body-colour variations in lepidopteran insects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of camouflage, the EUB Dark phenotype is also likely to be a poor combination, as a distinctly dark apex on an otherwise white shell is conspicuous. Whatever the exact mechanism is, the rarity of the EUB Dark combination contrasts with the highly flexible combinations of colour and banding in the supergene of C. nemoralis (Cook, 2005), but parallels similar rarities in other land snails (for example, Murray and Clarke, 1976a,b;Asami and Asami, 2008) and mimetic butterflies (for example, Clarke and Sheppard, 1969;Joron et al, 2006). By contrast, the other three morphs have potential advantages.…”
Section: Interaction Of Apex Colour and Shell Bandingmentioning
confidence: 93%
“…Indeed, the extent of sequence divergence and LD between the ZAL2 forms, revealing the suppression of recombination and their long-term coexistence, suggests that both functional haplotypes are actively maintained, and it was suggested that they might encode coadapted combinations of multiple traits (Falls and Kopachena, 1994;Romanov et al, 2009)-a form of giant supergene combining behavioural as well as plumage variation (Mather, 1950;Clarke et al, 1968;Joron et al, 2006). One remarkable finding is indeed the sheer number of genes locked into very large non-recombining units maintained by balancing selection.…”
mentioning
confidence: 99%